Frequency of Ethnicity and Causative Factors of Hepatocellular Carcinoma - Abdul Ghani Rahimoon, Sajan Sawai, Hira Laghari, Nand Lal Seerani, Zaheer Hussain Memon, Shabana Lakho (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of ethnicity and other etiological factors of hepatocellular carcinoma. Methodology: This cross-sectional study was conducted at the Liaquat University Hospital Hyderabad, Department of gastroenterology. The study occurred from March 2018 to February 2019 for a total period of one year. All the patients diagnosed as the cases of hepatocellular carcinoma; age more than 20 years of both genders were included. All the patients were assessed regarding their ethnicity and risk factors of hepatocellular carcinoma. A self-made study proforma was used for the data collection and data was analyzed by using the SPSS version 26. Results: A total of 80 patients of hepatocellular carcinoma were studied, their average age was 53.12+9.69 years, average CLD known duration was 05.40+3.90 years and the average known duration of HCC was 01.17+0.79 years. Males were in majority 76.3% and 40.0% of the cases had advanced disease. According to the ethnicity of the cases, Sindhi patients were 70.0%, followed by 6.3% were Punjabi, 1.3% were Pathan, 7.5% were Baloch and 15.0% were others. HCV was the most common cause 83.8%, 7.5% cases had HBV, followed by 2 cases had HBV+HDV and one case had HCV and HBV co-infection, while four cases were NBNC HCC patients. Tumor stage was statistically insignificant according to ethnicity (p-0.495). Conclusion: Sindhi and Punjabi population was observed to be mostly affected and HCV was concluded the most common causative factor of hepatocellular carcinoma. Keywords: Ethnicity, causes, HCC